2023
DOI: 10.3390/su15021418
|View full text |Cite
|
Sign up to set email alerts
|

Solar Energy: Applications, Trends Analysis, Bibliometric Analysis and Research Contribution to Sustainable Development Goals (SDGs)

Abstract: Over the past decade, energy demand has witnessed a drastic increase, mainly due to huge development in the industry sector and growing populations. This has led to the global utilization of renewable energy resources and technologies to meet this high demand, as fossil fuels are bound to end and are causing harm to the environment. Solar PV (photovoltaic) systems are a renewable energy technology that allows the utilization of solar energy directly from the sun to meet electricity demands. Solar PV has the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 99 publications
(110 reference statements)
1
12
0
Order By: Relevance
“…However, contrary to their work where the ocean energy is regarded as a renewable technology that can complement the future electricity system, this paper does not record a significant impact of ocean energy on the explanation of water‐energy nexus. These findings of the paper where solar PV is reported as a powerful technology, and SDG4 and SDG5 have relatively low outer weights compared with other ones generally show similarity with the ones in the study by Obaideen et al (2023), which reveals the lack of research in solar energy regarding those SDGs.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 82%
See 1 more Smart Citation
“…However, contrary to their work where the ocean energy is regarded as a renewable technology that can complement the future electricity system, this paper does not record a significant impact of ocean energy on the explanation of water‐energy nexus. These findings of the paper where solar PV is reported as a powerful technology, and SDG4 and SDG5 have relatively low outer weights compared with other ones generally show similarity with the ones in the study by Obaideen et al (2023), which reveals the lack of research in solar energy regarding those SDGs.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 82%
“…In their study using the snowballing approach, Hoosain et al (2023) revealed that a transition from a linear economy to a circular economy and newer Fourth Industrial Revolution digital technologies can positively back up the climate–water–energy–food nexus and also handle the UN‐SDGs ‐particularly SDGs 7, 8, 9, 11, 12, and 13‐ in a direct manner. Obaideen et al (2023) identified the bibliometric analysis regarding the solar PV system applications and technologies ‐Large‐Scale Solar PV”, “Residential Solar PV”, “Green Hydrogen”, “Water Desalination” and “Transportation”‐ as associated with SDGs for the period 2011–2021. Analyzed 126,513 papers reveal that solar energy researches predominantly focus on SDG7 and SDG13 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of modern solar photovoltaic systems fall under the first generation, utilizing silicon as their semiconductor material. These cells are renowned for their efficiency and durability, making them valuable for residential and commercial applications [40,46]. However, the disadvantage of these technologies is their high cost [44].…”
Section: Solar Energymentioning
confidence: 99%
“…Thin-film solar cells are commonly used in buildings and small PV systems [47]. Their widespread use is limited by their shorter lifetime and/or the use of highly toxic components [46]. Presently, solar PV technologies have made significant advancements, and various types of third-generation solar PV cells are being developed.…”
Section: Solar Energymentioning
confidence: 99%
“…Standalone, hybrid, and grid-connected PV systems will play an important role in the transition to a sustainable environment in the future [4]. Grid-connected PV systems allow end-users of electricity, communities, and small factories to generate electrical energy from the sun.…”
Section: Introductionmentioning
confidence: 99%